OPTIMASI NANOKAPSUL ASPIRIN YANG TERSALUT KITOSAN– GOM GUAR YANG DIPAUT SILANG DENGAN NATRIUM TRIPOLIFOSFAT - Surya Ningsi; Ismail Ismail; Andi Ulfiana Utari (Universitas Islam Negeri Alauddin Makassar, 2014)
A researched has been done about optimation of chitosan – guar gum crosslinked with sodium tripolyphosphate as coating agents nanocapsule aspirin. The researched purposed to get the best coating aspirin adsorption is based from observation of morpology and effisiency encapsulation.Nanocapsule formulations made with ionic gelation methods, using variation concentration of chitosan (1,5%, 1,75%, 2%), guar gum (0,75%, 0,55%, 0,35%), with fixed concentration of sodium tripolyphosphate (5%). Nanocapsules aspirin was measured using UV-Vis Spectrophotometry at a wavelength of 287 nm. Observation of the shape and size of the particles was performed using SEM (Scanning Electron Microscope). Encapsulation Effisiency obtained from formula A, B, and C of 28%, 52,6%, and 31,2%. Formula with chitosan concentration 1,75%, 0,55% guar gum, and 5% sodium tripolyphosphate (Formula B) has the best characteristics of the encapsulation effisiencyof 52,6%, the not sferis shape of the particles and more uniform thet the smallest particles size was 400 nm and the largest particle size was 2400 nm.